Az egyházzene mint közfelelősség - PAP, Ferenc (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Church Music as Public Responsibility. Public responsibility means, that an entity (institution, university, as well as the Church) has an obligation, a duty to act for the benefit of its social context, and for the promoting of the society. Church music has a character of public responsibility, and the duty of contributing to the teaching, service, and mission of the Church. The Synod of the Reformed Church in Hungary exercises the right of ius reformandi and ius liturgicum. Liturgical books, Hymnals, and the official translation of the Holy Scripture can be exclusively accepted and introduced by the Synod. This is a clear expression of public responsibility. A clear distinction between Church music and religious music has to be made. This study deals with the historical and the theoretical aspects of public responsibility concerning Church music.